Dampak Pengeboran Minyak Tradisional terhadap Degradasi Lingkungan Masyarakat di Desa Rantau Peureulak - Putra Al Haris; Dara Aisyah (Jurnal Hukum dan Sosial Politik, 2026)
This study aims to analyze the impact of traditional oil drilling activities on the environment and examine the local government's policy response in Rantau Peureulak Village. The growing traditional oil drilling activities in the area not only provide a source of livelihood for the community but also give rise to increasingly complex environmental problems. This study used a qualitative case study approach. Data were collected through field observations, semi-structured interviews with 10 informants consisting of village officials, drilling operators, affected communities, and related parties, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, using triangulation techniques to ensure data validity. The results indicate that traditional oil drilling activities have an impact on environmental degradation, particularly water and soil pollution around the drilling site. This is indicated by changes in the quality of community well water and soil contamination by oil waste. Community perceptions of these impacts tend to vary, with some recognizing the environmental damage but still relying on these activities as their primary source of income. Meanwhile, the local government's policy response is considered suboptimal, particularly in terms of oversight and policy implementation on the ground. Theoretically, these findings indicate that existing public policies have not been effective and responsive in addressing environmental issues, necessitating more comprehensive regulatory and oversight strengthening efforts. Therefore, local governments need to establish drilling zoning, increase oversight, and provide community development to minimize environmental impacts.